Halal Critical Material Analysis of Dental Bone Graft in the Indonesian Market: Implications for Clinical Decision-Making - Ridhayani Hatta; Mohamad Arif Budiman Putra Pratama; Nurfianti Nurfianti; Fathimah Azzahra; Wastuti Hidayati Suriyah; Dede Arsista; Solachuddin Jauhari Arief Ichwan (UIN Sunan Gunung Djati Bandung, 2026)
The integration of halal principles in the selection of bone graft materials, remains insufficiently studied. In Indonesia, is essential for meeting technological and ethical standards. In Indonesia, no structured framework currently exists to assess the halal criticality of commercially available bone graft products. This study aimed to analyze the potential presence of halal-critical materials in dental bone grafts available in the Indonesian market. An observational descriptive study was conducted on 16 commercial dental bone graft products classified into five categories: allografts, xenografts, alloplasts, growth factors, and composite grafts. Product compositions were identified using Material Safety Data Sheets (MSDS), Chemical Abstracts Service (CAS) numbers, and manufacturer disclosures, and evaluated against the Halal Positive List issued by LPPOM MUI. The results showed that alloplasts exhibited the lowest halal criticality, as they consist solely of synthetic, non-animal, and non-human materials. Conversely, xenografts and allografts demonstrated higher halal risk due to animal and human-derived components, while growth factors and composite grafts showed variable risk profiles. This study provides a material-based halal criticality analysis to support clinical decision-making and underscores the need for clearer halal regulatory guidance for dental biomaterials in Indonesia.